Later high school start times associated with longer actigraphic sleep duration in adolescents - Nicole G. Nahmod; Soomi Lee; Lindsay Master; Anne‐Marie Chang; Lauren Hale; Orfeu M. Buxton (2018)
High school start times (SSTs) directly impact adolescents' sleep timing and duration. This study investigated the associations between SSTs and actigraphically-measured 24-hour sleep duration, sleep onset, sleep offset and sleep quality. This study included 383 adolescents (Mage = 15.5, SDage = 0.6 years) participating in the age 15 wave of the Fragile Families & Child Wellbeing Study, a national birth cohort study sampling from 20 large US cities. Multilevel models used daily observations (N = 1116 school days, Mdays = 2.9, SDdays = 1.4 per adolescent) of sleep and SSTs from concordant daily diary and actigraphy. A diverse range of SSTs were included in our analyses (MSST = 08:08, SDSST = 39 minutes, RangeSST = 06:00–11:05), and are presented in the following categories for ease of interpretation: before 07:30, 07:30–07:59, 08:00–08:29, and 08:30 or later. Adolescents starting school at 08:30 or later exhibited significantly longer actigraphically-assessed 24-hour sleep duration (by 21–34 minutes, p < .05) and later sleep offset (by 32–64 minutes, p < .001) when compared with the adolescents grouped by earlier SSTs. SSTs were also analyzed continuously for comparison with existing literature, and results indicated that every 1-hour delay in SST was significantly associated with 21 minutes longer 24-hour sleep duration (p < .001), 16 minutes later sleep onset (p < .01), and 39 minutes later sleep offset (p < .001). All models controlled for covariates including socioeconomic status. These findings support pediatric and public health expert recommendations for SSTs after 08:30. In our diverse national urban sample, adolescents with SSTs at 08:30 or later, compared with adolescents with earlier SSTs, had significantly longer actigraphy-measured sleep.